A terpolymeric hydrogel of hyaluronate-hydroxyethyl acrylate-gelatin methacryloyl with tunable properties as biomaterial. (1st March 2019) - Das, Dipankar; Cho, Hana; Kim, Nahye; Pham, Thi Thu Hien; Kim, In Gul; Chung, Eun-Jae; Noh, Insup
Graphical abstract: Highlights: Hyaluronate-based terpolymeric gel was synthesized and physicochemically analysed. In vitro cell study showed chondrocytes survival and promotion of cell behaviours. In vivo biocompatibility was confirmed using mouse model. The hydrogel releases bovine serum albumin and dexamethasone in a sustain way. Abstract: Here, we report synthesis of a terpolymeric covalently crosslinked hydrogel of hyaluronate (HA) as biomaterial with elasticity, mechanical properties and cell interactions via conventional free radical polymerization technique. To provide elasticity and mechanical properties, 2-hydroxyethyl acrylate (HEA) was grafted in HA, while to tune cellular interactions, gelatin methacryloyl (GM) was used as crosslinker. The composition and probable structure of the terpolymer (HA-g-pHEA-x-GM) were analysed by FTIR, 1 H HR-MAS-NMR, and TGA analyses. The SEM and texture analyses of hydrogel showed interconnected micro-porous network and high mechanical properties, respectively. In vitro biocompatibility was studied against human chondrocytes, whereas, in vivo biocompatibility and tissue regeneration were confirmed using mouse model. The hydrogel releases model protein-bovine serum albumin, and corticosteroid drug-dexamethasone in a sustain way at pH 7.4 and 37 °C. Overall, the tunable mechanical properties, micro-porous network, and cytocompatibility of the HA-g-pHEA-x-GM hydrogel highlights its potential applicability in cartilage tissue engineering and drug delivery.